Quantitative Analysis of Non-timber Forest Products in Four Forest Types of Pacchaimalai Hills, Eastern Ghats, Tamil Nadu - Britto, S. John; Soosairaj, S.; Balaguru, B.; Arockiasamy, D. I. (Indian Forester, 2003)
Collection of Non-Timber Forest Products from reserved forest is on the increase, as there is a growing exploitation from the ever-expanding tribal population. The present study aims at a quantitative analysis of NTFPs in 0.12 ha area of four forest types of Pacchaimalai Hills, Eastern Ghats (Tamil Nadu). Density, frequency and abundance of trees, lianas, shrubs, climbers and herbs have been calculated. A total of 5,760 ha-1 individuals of NTFPs plants from 86 species of 80 genera and 40 families have been recorded. The result indicates that the diversity of NTFPs plants is higher in the Semi-evergreen forest type followed by the Dry deciduous type.